Taxonomic updates on Pachyserica Brenske, 1898 and Serica MacLeay, 1819 reveal 38 new species and new challenges of Sericini systematics regarding DNA barcodes and genus-level diagnostic key characters (Coleoptera: Scarabaeidae: Sericinae) - Ahrens, Dirk; Zhao, Ming-Zhi; Pham, Phu Van; Liu, Wan-Gang (Zootaxa, 2024)
Here we present updates on the taxonomy and distribution of the genera Pachyserica Brenske, 1898 and Serica MacLeay, 1819 from East Asia. Thirty eight new species are desribed from China, Myanmar, South Korea, and Vietnam: Pachyserica chenchangchini Ahrens, Zhao, Pham & Liu, new species, P. dieuthuyae Ahrens, Zhao, Pham & Liu, new species, P. hoabinhensis Ahrens, Zhao, Pham & Liu, new species, P. motuo Ahrens, Zhao, Pham & Liu, new species, P. natmatoung Ahrens, Zhao, Pham & Liu, new species, P. sanqingshanensis Ahrens, Zhao, Pham & Liu, new species, P. sunfengyii Ahrens, Zhao, Pham & Liu, new species, P. tayyentu Ahrens, Zhao, Pham & Liu, new species, P. tianxuani Ahrens, Zhao, Pham & Liu, new species, P. wangzizhaoi Ahrens, Zhao, Pham & Liu, new species, P. yaonani Ahrens, Zhao, Pham & Liu, new species, P. yinhengi Ahrens, Zhao, Pham & Liu, new species, P. zhanbaoxiangi Ahrens, Zhao, Pham & Liu, new species, Serica (s. l.) anhua Ahrens, Zhao, Pham & Liu, new species, S. (s. l.) camura Ahrens, Zhao, Pham & Liu, new species, S. (s. l.) fengxue Ahrens, Zhao, Pham & Liu, new species, S. (s. l.) nhiae Ahrens, Zhao, Pham & Liu, new species, S. (s. l.) paracallosericoides Ahrens, Zhao, Pham & Liu, new species, S. (s. l.) taythien Ahrens, Zhao, Pham & Liu, new species, S. (s. l.) wuyishan Ahrens, Zhao, Pham & Liu, new species, S. (s. l.) yuechengling Ahrens, Zhao, Pham & Liu, new species, S. (Serica) assingi Ahrens, Zhao, Pham & Liu, new species, S. (S.) bomi Ahrens, Zhao, Pham & Liu, new species, S. (S.) christophreuteri Ahrens, Zhao, Pham & Liu, Ahrens, Zhao, Pham & Liu, new species, S. (S.) cuona Ahrens, Zhao, Pham & Liu, new species, S. (S.) fansipan Ahrens, Zhao, Pham & Liu, new species, S. (S.) gongtonggouensis Ahrens, Zhao, Pham & Liu, new species, S. (S.) guangxiensis Ahrens, Zhao, Pham & Liu, new species, S. (S.) gwangjuensis Ahrens, Zhao, Pham & Liu, new species, S. (S.) hongyii Ahrens, Zhao, Pham & Liu, new species, S. (S.) jiangda Ahrens, Zhao, Pham & Liu, new species, S. (S.) jiulaoci Ahrens, Zhao, Pham & Liu, new species, S. (S.) lushui Ahrens, Zhao, Pham & Liu, new species, S. (S.) liyitengi Ahrens, Zhao, Pham & Liu, new species, S. (S.) qizhihaoi Ahrens, Zhao, Pham & Liu, new species, S. (S.) xizang Ahrens, Zhao, Pham & Liu, new species, S. (S.) zhamu Ahrens, Zhao, Pham & Liu, new species, and S. (Taiwanoserica) yexiaohani Ahrens, Zhao, Pham & Liu, new species. The lectotype of Pachyserica scalaris Arrow, 1946 is designated and its male genitalia is illustrated. Additional records of 66 other species are provided.